Production of sustainable methanol from plastic wastes by green energy to optimize landfill area / Dineshini Ganeshmoorthy - Dineshini, Ganeshmoorthy (2022)
The fundamental element required to produce methanol is syngas. Many researchers have carried out in depth experiment on using plastic wastes to draw syngas which can be turned into methanol. Howbeit, the process of making this alternate fuel should be taken into consideration in order to attain sustainability. Exploiting the plastic wastes into a pyrolysis system that converts into methanol could reduce the expansion of landfill problem while contributing to alternate fuel. However this does not make the whole system sustainable unless the electricity required to operate is drawn from renewable source. In this paper, a thorough study showed on the possibilities of making the methanol production sustainable by substituting the raw material into plastic. Besides, the obsolete concept of energy storage system will be presented explaining how it could contribute to sustainable methanol production. On the other hand, based on the data collected from other research papers, the total amount of methanol that can be produced from the plastic wastes generated daily will be calculated. The propagation of plastic weightage to produce 1 litter of methanol was attained from an experiment conducted at a R & D chemical located at Kajang. From this calculation, a presumption were showed on the geographical layout that about 1/3 of the landfill area were saved. There are innumerable landfills been operating in Malaysia. Thus to explain the land reduction at landfill, Pulau Burung Landfill, Penang will be taken as an example to demonstrate by inserting the boundary coordinates of the overall location along with reduced landfill area location using polygon features in the GQIS software. The overall land and optimized land will be exemplified from the geographical image obtained from QGIS software. Considering this approach will be elucidated on how it greatly affect the Malaysia’s economic and environment.